Analyzing critical success factors for a successful transition towards circular economy through DANP approach. Issue 3 (4th March 2020) - Khan, Shahbaz; Maqbool, Annayath; Haleem, Abid; Khan, Mohd Imran
Abstract : Purpose: The successful transition towards the circular economy is a requirement of this technological era. The objective of this study is to identify critical success factors behind the successful transition to the circular economy. Design/methodology/approach: A systematic literature review and experts' inputs are used to identify the major critical success factors of a successful transition towards a circular economy. Further, DANP is applied to discover the interrelationships among the critical success factors dimensions by analyzing causal relations between the relevant critical success factors. Additionally, the ranking of significant critical success factors for the successful transition towards the circular economy is determined. Findings: This study has used the DANP methodology to understand the relationships among the five dimensions and the twenty-two critical success factors and identified the key influencing critical success factors through their global weights. Research findings suggest that "vision regard to a circular economy" has the highest weights, followed by "financial sustainability" which is regarded as the most important CSF. Research limitations/implications: The outcomes of this work may help organizations on issues related to the transition of the linear economy towards circular economy, in understanding the degree of importance of the each critical success factors, based on which the organizations can formulate an effective strategy to systematically emphasize critical success factors as per their importance for the successful transition towards circular economy. Originality/value: This study tries to explore and analyze critical success factors of the transition from the linear economy to a circular economy. Further, the finding of this study provides deeper insights into academia and mangers that helps to formulate their action plan for moving towards the circular economy.